A comparative study between olive oil and Nigella Sativa oil in treatment of hyperlipidemia induced in male albino mice - Kafi, Lubna Ahmed (The Iraqi Journal of Veterinary Medicine, 2014)
This study was conducted on 20 adult mice which were divided randomly in to 4 equal groups. The first group served as negative control (NC) that received the diluent (sun flower oil), while hyperlipidemia was induced in the other three groups, the second group received the diluent and considered as positive control (PC), while group three and four were treated with olive oil (OO) or Nigella sativa oil (NSO) at a dose of 0.4ml/kg BW orally, respectively for two months. At the end of experiment and fasting overnight, lipid profile which included (total cholesterol TC, triglyceride TG, high density lipoprotein cholesterol HDL-C, low density lipoprotein cholesterol LDL-C and very low density lipoprotein cholesterol VLDL-C) were measured. The results indicated significant (P<0.05) improvement in all these parameters as compare to the positive control, while the value of HDL-C was significantly higher in the olive oil treated group as compared with all groups including negative control group.